2005
DOI: 10.4049/jimmunol.174.5.2619
|View full text |Cite
|
Sign up to set email alerts
|

Activated Human B Lymphocytes Express Cyclooxygenase-2 and Cyclooxygenase Inhibitors Attenuate Antibody Production

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used for the treatment of inflammatory diseases and target cyclooxygenases 1 and 2 (Cox-1, Cox-2) that are responsible for PG production. Newer Cox-2-selective drugs have been heavily prescribed to quench inflammation. Little is known about whether or not these drugs influence human B lymphocytes and their ability to produce Ab. We report herein that activated human B cells not only highly express Cox-2 and produce PGs, but that the NSAID indomethacin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 32 publications
6
108
0
Order By: Relevance
“…We have found that spontaneously activated lupus B cells constitutively express high levels of COX-2, as do mitogenically stimulated, normal human B cells (40,41). Interestingly, CD86 high (activated) B cells from SNF 1 mice expressed more COX-2 than did the same subset from nonautoimmune strains, indicating a lupus-intrinsic defect (Figure 4).…”
Section: Discussionmentioning
confidence: 89%
“…We have found that spontaneously activated lupus B cells constitutively express high levels of COX-2, as do mitogenically stimulated, normal human B cells (40,41). Interestingly, CD86 high (activated) B cells from SNF 1 mice expressed more COX-2 than did the same subset from nonautoimmune strains, indicating a lupus-intrinsic defect (Figure 4).…”
Section: Discussionmentioning
confidence: 89%
“…For control studies, the same purification method was used in conjunction with uninfected SF9 cells; this preparation was then used as a negative control. Analogous to our previous reports (28,29) and that of others (27), the concentrations of CD40L used in experimental analyses are described in terms of the relative dilution of the CD40L-containing stock prepared.…”
Section: Reagentsmentioning
confidence: 98%
“…To date, results have been mixed, with one study showing that indomethacin inhibited antibody production without loss of cell viability. However, other studies showed that NSAIDs decreased antibody secreting cells 61 or resulted in a modest reduction in B cell proliferation without inducing apoptosis. 49 Overall, antipyretic analgesics actions on cells and on signaling pathways appear to be diverse and studies to date have shown opposing effects.…”
Section: Mechanisms Of Antipyretic Analgesics Action On the Immune Symentioning
confidence: 98%
“…60 COX-1 and COX-2 inhibitors have been shown to markedly reduce antibody production. [61][62][63] Human B cells strongly express COX mRNA and protein and produce prostaglandins upon activation 61 suggesting a potential target for antipyretic analgesics in antibody producing cells. However, this reduction was also observed in COX-deficient mouse models, 49,61 indicating that the mechanism is not solely dependent on that pathway.…”
Section: Mechanisms Of Antipyretic Analgesics Action On the Immune Symentioning
confidence: 99%